PEMANFAATAN RUBRIK BERITA UTAMA SURAT KABAR SOLOPOS SEBAGAI MATERI AJAR BAHASA INDONESIA DI SMP - Yusuf Cahyo Saputro; Atikah Anindyarini; Chafit Ulya (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to describe the use of euphemism and dysphemism in the Solopos newspaper headlines as Indonesian teaching material in junior high schools. This research is a descriptive qualitative research with content analysis method. The data source used was the headline of the December 2019 edition of the Solopos newspaper, which contained expressions of euphemism and dysphemism. The data analysis technique used is the flow analysis model. Data validity test used is theory triangulation, data source triangulation, and informant review. Data collection techniques used were document analysis and in-depth interviews. informants in this study were Indonesian Language teachers and junior high school students. The results of this study indicate that the use of the main news rubric in the Solopos newspaper can be used as teaching material for writing news texts using one of the two stay two stray learning models.